ISTILAH KEKERABATAN DALAM MASYARAKAT BANYUWANGI (TERMS OF KINSHIP IN THE BANYUWANGI SOCIETY) - Puspa Ruriana (Balai Bahasa Sulawesi Utara, 2018)
Kinship is a term to mention or greet someone who is bound to ourselves because of descent, blood, and marriage. In the Banyuwangi society, it is known terms of kinship, which is not found in the other society in east Java. The research purposes are to describe the terms of kinship and their functions to Banyuwangi society. The problem of the research is how the using of the terms kinship and the function in the daily using in Banyuwangi society. The method of the research is participant observation. Padan method is used to analyzes data which are found. Data are colected by interviewing the informants and also it is supported by recording and writing technique. Data is analyzed using kinship system theory. Kinship terms in the Banyuwangi society can be grouped in to three, the kinship terms because of direct line of descent, kinship terms because of indirect line of descent, and kinship terms because of marriage. The function of the terms kinship in the Banyuwangi society in addition to showing kinship relations, it also functions claimed to be brothers.